Optimalisasi Pembelajaran dan Komunikasi Keluarga di SMA Al Hadi Melalui Evaluasi Kognitif dan Intervensi Terpadu - Anissaniwaty, Myrna; Widyastuti, Linda; Hakim, Alfi Fauzia; Panjaitan, Yoko Jimmy; Rambe, Ira Hasianna; Nur’aeni, Siti; Ardiva, Elsya; Abdul Jabar, Raihan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Challenges in education and family dynamisc often hinder optimal learning and development among students. They face difficulties in focusing during lessons and comprehending instructions, resulting in suboptimal academic performance. Objective: The purpose of this service was to enhance student;s cognitive abilities, focus, and emotional well being while also empowering parents to adopt effective communication strategies to foster a supportive learning environment. Method: This public service was conducted by through several stages, including administering the Faxtor Cognitive Ability Test (FCAT) to assess student’s cognitive skills. Workshop for innovative learning and entrepreneurship were organized for student and teacher. For parents, a psychoeducation sessions were conducted to enhance their communication strategies with their children. Result: The activities showed a positive impact, with students demonstrating increased focus and engagement during learning sessions. The workshops provided a platform for students to improve their communication, problem-solving, and teamwork skills Conclusion: This community service initiative successfully addressed critical issues at SMA Al Hadi by enhancing students’ cognitive and social skills while equipping parents with effective communication tools. These results underscore the potential for replicating similar programs in other schools facing comparable challenges.